Schools as dangerous places: a historical perspective - Potts, Anthony; O'Donoghue, T. A. (Cambria Press, 2007)
Schools as dangerous places : preliminary considerations / T. O'Donoghue and A. Potts -- Legal aspects of schools as dangerous places / A. Potts -- Sporting violence in Australian public schools, 1850-1914 / M. Crotty -- The abuse of children in Irish charter schools in the early 19th century / M. Coleman -- "Illicit" sexuality and public education in Ontario, 1840-1907 / B. Curtis -- Magdalen asylums and moral regulation in Ireland / B. Titley -- Teachers and the child-abuse scandals in Catholic schools / T. O'Donoghue -- Dealing with the sexual harassment of teachers in the classroom in the early twentieth century / J. Jose and C. Bacchi -- The rise and fall of a significant headmaster / M.D. Prentis -- Outcasts of the Orkney (and other) Islands : abusive Scottish insular teachers -- 1872-1945 / D. Limond -- Young teachers and corporal punishment in inter-war elementary schools in Britain / P. Gardner -- Eugenicists, doctors, and education in Britain, 1900-1939 / R. Lowe -- Hazing in a US university from 1868 to 1913 / W. Solberg -- The dismissal of a distinguished sociologist / O.F. Larson, R.M. Williams Jr., and R.C. Wimberley -- University colleges as dangerous places / A. Potts